Analyzing the Impact of State Fragility, Trade Openness, and Labor Force on Foreign Direct Investment in ASEAN: An Islamic Economic Perspective (2013-2022) - Alliena Fathi Amrullah; Madnasir; Okta Supriyaningsih (Journal of Islamic Finance and Economic Studies, 2025)
Background: Foreign Direct Investment (FDI) plays a significant role in the economies of developing countries, including those in the ASEAN region. Factors such as state fragility, trade openness, and labor force are believed to significantly influence FDI inflows. This research examines the relationship between these three factors and FDI inflows in 9 ASEAN countries from 2013 to 2022, with an Islamic economic perspective. Aims: This study aims to analyze the impact of state fragility, trade openness, and labor force on FDI inflows in 9 ASEAN countries from 2013 to 2022, and to provide insights into the Islamic economic perspective on foreign direct investment. Methods: This study employs a quantitative approach using panel data analysis. Secondary data is collected from the official World Bank website and the Fragile States Index. Data analysis is conducted using t-tests, F-tests, and R2 coefficient determination to test the relationships between the independent variables and FDI. Results: The results of this research show that state fragility has a negative but insignificant effect on FDI. Meanwhile, trade openness and the labor force have a positive and significant effect on FDI inflows in the ASEAN region. Conclusion: Trade openness and labor force play a key role in attracting FDI in ASEAN countries, while state fragility does not significantly affect foreign investment. From an Islamic economic perspective, FDI should not only be viewed as a way to increase individual wealth but also as a means to support inclusive economic growth and societal development.